(3GdJHUjQ aj GdaQbs - (3CHh GdeXaQ WGgQ Hf eMeO GdESaQGjjfj,J (B471 (3g` s
(3ChdgG (B:s
(3QShd Gddg Udi Gddg Ydjg hSde GdaQbI GdChdi efge GdMcejI GdChdi hChd ef bGd efge dYdi cQe Gddg hLgg dGMce EdG ddg YQhg Hf LQjQ s
(3BNQgG (B:s
(3hde jJab dCMO ef GdCFeI ai TF ef GdYdhe heKd Pdc GdcJGH hef MSf EMcGeg Gfg dGWQjb dCMO ef GdeNGda hGdehGab Edi fbVg QDha QMje Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B223s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B340s
Keywords: (3GdJhMjO hGdedd hGdfMds